THE DEVELOPMENT NATURAL SCIENCES BASED ADOBE FLASH CS3 WITH THE TOPIC SYSTEM OF COORDINATION AND THE SENSES IN HUMANS IN NINTH GRADE JUNIOR HIGH SCHOOL - PEPI MIRDAYANTI; TRY SUSANTI; VANDRI AHMAD ISNAINI (Sriwijaya University Learning and Education International Conference, 2016)
The purpose of this study was to develop a product in the form of instructionalmedia based integrated natural science adobe flash cs3. This research is thedevelopment or R & D by adopting a 4-D model of development, namely, the stageof defining, designing, and development. Samples were students of class IX juniorhigh school. Data was collected using a questionnaire sheet that covers severalaspects of the study include: feasibility aspects of the material / content, language,presentation and evaluation. Quality media rated by the media experts, subjectmatter experts and language and class IX students of junior high school.